CLASSROOM MANAGEMENT AND STUDENT GROUPING (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Effective classroom management is widely regarded as a cornerstone of successful teaching and learning. Within this framework, student grouping plays a significant role in shaping learner engagement, behavior, and academic outcomes. This article explores the theoretical foundations, practical strategies, and challenges associated with classroom management and student grouping. Drawing on pedagogical theories such as Communicative Language Teaching, Constructivism, and Social Interdependence Theory, the article argues that intentional grouping enhances participation, collaboration, learner autonomy, and equitable learning opportunities. It also discusses practical techniques for establishing classroom routines, organizing physical space, minimizing disruptions, and ensuring productive group interaction. The article concludes that combining strong management strategies with purposeful grouping fosters a conducive learning environment that supports cognitive, social, and emotional development.